Valuasi Ekonomi Hutan Tele Di Kabupaten Samosir - Dharma Yoga Putra Simbolon; Yunus Afifuddin; Siti Latifah (Program studi Kehutanan USU, 2015)
Tele forest mostly used by people around the forest, but they have not been informed about important values ​​and meaning of the forest, they generally only know how to take or make use of forest products based on their own knowledge from generation to generation, without knowing the proper way to preserve the forests and existence. Based on that, it needs an evaluation to determine the importance of forests to society, the values ​​contained in it and how the development strategy for forest conservation Tele. To that end, research on the Economic Valuation of Forest Tele Samosir district has done in November to December 2014 This study used interviews and direct measurements in the field to determine the economic value of forests and determine the factors that influence it. Data obtained from respondents are tabulated, then used as an analysis to determine the total economic value of forests and to determine the factors that influence it. The total economic value of Tele forest is Rp 806.357.253.000 / year or Rp 11,962,692 / year / ha. Economic values ​​contained in Tele forest is direct benefits in the form of firewood forests, orchids, andaliman and indirect forest benefits such as the value of household water, irrigation water value, the value of carbon sequestration as well as the option value and existence value. Keywords : Tele forest valuation, forest benefits, the economic value of forest